Mapping local patterns of childhood overweight and wasting in low- and middle-income countries between 2000 and 2017 - Kinyoki, Damaris K.; Schutte, Aletta E.; Ross, Jennifer M.; Lazzar-Atwood, Alice; Munro, Sandra B. (Springer Nature, 2020)
A double burden of malnutrition occurs when individuals, household members or communities experience both undernutrition and overweight. Here, we show geospatial estimates of overweight and wasting prevalence among children under 5 years of age in 105 low- and middle-income countries (LMICs) from 2000 to 2017 and aggregate these to policy-relevant administrative units. Wasting decreased overall across LMICs between 2000 and 2017, from 8.4% (62.3 (55.1-70.8) million) to 6.4% (58.3 (47.6-70.7) million), but is predicted to remain above the World Health Organization's Global Nutrition Target of <5% in over half of LMICs by 2025. Prevalence of overweight increased from 5.2% (30 (22.8-38.5) million) in 2000 to 6.0% (55.5 (44.8-67.9) million) children aged under 5 years in 2017. Areas most affected by double burden of malnutrition were located in Indonesia, Thailand, southeastern China, Botswana, Cameroon and central Nigeria. Our estimates provide a new perspective to researchers, policy makers and public health agencies in their efforts to address this global childhood syndemic